2018
DOI: 10.1007/s10646-018-1937-1
|View full text |Cite
|
Sign up to set email alerts
|

A long-term field study on the effects of dietary exposure of clothianidin to varroosis-weakened honey bee colonies

Abstract: Clothianidin is a commonly used systemic insecticide in seed treatments. Residues of clothianidin can occur in nectar and pollen as a result of within-plant-translocation. Foraging bees can collect contaminated nectar or pollen. Concerns have been brought forward that exposure to pesticide residues might affect colonies especially if they are weakened by varroosis. However, there are few scientific studies investigating such multiple-stressor scenarios in the context of the entire colony. To close this gapa fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The surviving honeybee colonies were placed for an additional season by the maize fields of the same treatment (control/clothianidin or thiamethoxam) and Varroa abundance was again higher in colonies placed by neonicotinoid-treated fields with low levels of neonicotinoid exposure confirmed for apiaries at treated sites and for one of two control apiaries 59 . Experimentally induced exposure of honeybees to both Varroa and clothianidin spiked syrup showed no interactive effect between the two pressures 31 . In another study, long-lasting in-hive feeding of thiacloprid to honeybee colonies did not affect colony performance or the levels of parasites, pathogens and expressed immunity-related genes 30 .…”
Section: Discussionmentioning
confidence: 84%
“…The surviving honeybee colonies were placed for an additional season by the maize fields of the same treatment (control/clothianidin or thiamethoxam) and Varroa abundance was again higher in colonies placed by neonicotinoid-treated fields with low levels of neonicotinoid exposure confirmed for apiaries at treated sites and for one of two control apiaries 59 . Experimentally induced exposure of honeybees to both Varroa and clothianidin spiked syrup showed no interactive effect between the two pressures 31 . In another study, long-lasting in-hive feeding of thiacloprid to honeybee colonies did not affect colony performance or the levels of parasites, pathogens and expressed immunity-related genes 30 .…”
Section: Discussionmentioning
confidence: 84%
“…Jones et al 30 demonstrated that although the gut microbial composition is influenced by the surrounding landscape, the relationship between environmental stressors, the gut symbiotic bacteria and its host is too complex and interactive for simple reductionist assessments. Two other field studies also found no effect of neonicotinoids on Varroa abundance 41,51 , while a third found a positive association 52 . In addition, in-hive feeding with imidacloprid-spiked pollen increased Varroa abundance but only at a very high imidacloprid concentration 49 .…”
Section: Discussionmentioning
confidence: 89%
“…In certain field studies, realistic exposure levels to insecticides do not harm the bees at the colony level. But, when investigated at individual level, insecticide-induced effect can be observed (Blacquiere et al 2012, Fischer et al 2014, Lundin et al 2015, Retschnig et al 2015, Odemer et al 2018, Siede et al 2018, Rolke et al 2016. Social resilience or buffering obviously plays a crucial role at colony level which is not possible at individual level and these mechanisms are not yet fully understood (Manjon et al 2018, Straub et al 2015.…”
Section: Introductionmentioning
confidence: 99%